Neuroimaging Features of Optic Nerve Hemangioblastoma Identified by Conventional and Advanced Magnetic Resonance Techniques: A Case Report and Literature Review - Duan, Meihan; Yang, Lie; Kang, Jun; Wang, Renzhi; You, Hui; Feng, Ming (Frontiers in Oncology, 2021)
Optic nerve hemangioblastoma is a very rare benign tumor with only 39 reported cases by now. It appears to be hyperintense on T2-weighted images with a significant enhancement on contrast scans, which are similar to glioma and meningioma. Due to the lack of specificity in MRI manifestations, optic nerve hemangioblastoma is often misdiagnosed. To provide new insights into differential diagnosis of optic nerve hemangioblastoma, we report for the first time an optic nerve hemangioblastoma case employing advanced magnetic resonance techniques including diffusion-weighted imaging (DWI), apparent diffusion coefficient (ADC) maps, and magnetic resonance angiography (MRA). In addition, we have collected all reported optic nerve hemangioblastoma cases and reviewed their neuroimaging findings by MRI and angiography. Our results show that solid-type tumor is the dominant form of optic nerve hemangioblastoma and extensive edema is widely observed. These findings are surprisingly contrary to manifestations of cerebellar hemangioblastoma. Besides the structural features, quantitative indexes including ADC and relative cerebral blood volume (rCBV) ratio, which are significantly elevated in cerebellar hemangioblastoma, may also shed a light on the preoperative diagnosis of hemangioblastoma of optic nerve. Finally, we discuss the critical neuroimaging features in the differential diagnosis between optic nerve hemangioblastoma from optic pathway glioma and optic nerve sheath meningioma.